Public Access Microcomputers: A Handbook for Librarians - Dewey, Patrick R. (White Plains Knowledge Industry Publications, Inc., 1984)
Public Access Microcomputers: A Handbook for Librarians. This is not a book about the many administrative or internal uses to which a microcomputer can obviously be put, such as catalog card and overdue notice production or circulation control.Forther, no effort will be made to give anyone a quick course in microelectronics or computer science, both of which are beyond the scope of this book.
Keywords: Teaching English